The Evolution of Innovation Networks: An Automotive Case Study - Buchmann, Tobias (Springer, 2015)
Tobias Buchmann analyzes innovation network dynamics in the German automotive industry. The study is based on a model for analyzing the complex evolution of innovation networks and the driving mechanisms underlying network evolution derived from theoretical and empirical findings in innovation economics, economic geography and management science. The author uses established social network analysis (SNA) techniques and combines them with recent methodological developments in the analysis of network evolution.